Total Factor Productivity Growth Based on Resource and Non Resource Based Industries of the Manufacturing Sector, 2000-2005 (Sains Humanika, 2013)
This paper examines total factor productivity (TFP) growth in resource and non resource based industries of the Malaysian manufacturing sector. The growth in TFP is examined between 2000 and 2005. Unlike previous studies that use one source of data from Industrial Manufacturing Survey (IMS), this research combines two sources of data–Malaysian Input-Output Tables and IMS. The motivation for this study was brought about due to the need to present a different method for estimating TFP growth using the input-output methodology. The result from this study for resource and non resource based industries reveals that the TFP growth is relatively low for both industries. In addition, the major source of change in TFP of the both industries is contributed by intermediate inputs, while the contribution of labour and capital is substantially low
Keywords: Total factor productivity growth; input-output methodology; resource and non resource based industries